Ireland : 2016 Sixth Post-Program Monitoring Discussions-Press Release; and Staff Report for Ireland. (IMF Staff Country Reports; Country Report ;, 2017)
This paper highlights the main points of 2016 Sixth Post-Program Monitoring Discussions with Ireland. Ireland continued to grow at a healthy pace in 2016, mainly driven by domestic demand. The current account surplus widened somewhat in the first three quarters of 2016. Exchequer data for December confirmed the positive trend in public finances. The headline general government deficit is expected to end the year on target at 0.9 percent of GDP, while the debt burden is on a steady downward path. Balance sheet repair of domestic banks has continued but profitability remains weak. Property market conditions have tightened further, mainly owing to a limited supply response.